Guru dan Pendidik dalam Perspektif Gurindam Dua Belas Karya Raja Ali Haji - Dahrani, Dahrani; Roza, Ellya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to analyze teachers and educators in the perspective of Raja Ali Haji's Gurindam Twelve Works. This type of research is a literature study. Data collection with documentation. Data analysis with SLR. The results of the research In Raja Ali Haji's Gurindam Dua Belas, teachers and educators are considered the main pillars in forming a civilized and cultured society. They are seen as lights on the path who guide the younger generation to acquire knowledge, noble morals and wisdom. Teachers not only teach knowledge, but also pay attention to the formation of students' character and morals. Educators in the perspective of Gurindam Dua Belas are seen as pillars of the intellectual and spiritual development of society, whose task is to educate students so that they can become individuals who are responsible, dignified and beneficial to society.